Synchronous Ipsilateral Pleomorphic Adenomas of Parotid and Submandibular Glands: An Unusual Finding - Walter Colangeli; Aleksandr Kapitonov; Valerio Facchini; Marta Zappalà; Evaristo Belli (Case Reports in Otolaryngology)
A rare case of synchronous ipsilateral pleomorphic adenomas (PA) of the left parotid and submandibular glands is reported. Simultaneous multiple PA in major salivary glands are a very rare entity, and merely few cases of ipsilateral synchronous PA involving parotid and submandibular glands are reported in the literature. The case of a 40-year-old female with a six-year history of asymptomatic growing lesion in both left parotid and left submandibular regions is presented. Left superficial parotidectomy and left submandibular gland excision at the same surgery have been performed. The aim of this article is to highlight the importance of an accurate head and neck presurgery examination both clinically and radiologically, keeping in mind the possibility of multiple tumor location.